2006
DOI: 10.1111/j.1365-2133.1995.tb05031.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic pustular folliculitis in infancy: report of two affected brothers

Abstract: Summary We describe two brothers with eosinophilic pustular folliculitis. Both had recurrent crops of papules and pustules, primarily affecting the scalp. The eruption began in the neonatal period. Both children had a leucocytosis with eosinophilia. Histology revealed folliculitis, with an infiltrate in which eosinophils were predominant. Bacteriological and fungal cultures of pustules were negative. There was a good clinical response to treatment with a topical corticosteroid and dapsone. We review the 28 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Regarding treatment, 51 of the 61 children were treated with low-to medium-potency topical steroids (83%), of whom 46 responded well, meaning that they were effective in 90% of cases in which their use was specified. Of the 5 nonresponders, 1 responded well to oral erythromycin, 3 2 required dapsone, 5,9 and in 2 additional cases the alternative treatment was not detailed. 2,14 Dapsone was effective in both cases, but had to be withdrawn in 1 case because of hematologic side effects.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding treatment, 51 of the 61 children were treated with low-to medium-potency topical steroids (83%), of whom 46 responded well, meaning that they were effective in 90% of cases in which their use was specified. Of the 5 nonresponders, 1 responded well to oral erythromycin, 3 2 required dapsone, 5,9 and in 2 additional cases the alternative treatment was not detailed. 2,14 Dapsone was effective in both cases, but had to be withdrawn in 1 case because of hematologic side effects.…”
Section: Resultsmentioning
confidence: 96%
“…These were isolated cases, 3,5,7 whereas many patients were treated ineffectively with antibiotics before being given the diagnosis. [2][3][4][5][6][7][8][9]11,12,14,15,17,19 The good response could be considered as coincidental, because the process tends to be self-limiting, even without treatment, 15,18 but some authors favor the antichemotactic activity of some antibiotics such as erythromycin. 7 Cetirizine has also been successfully used by some authors, who advocate its antieosinophilic activity and antipruritic effect, 3 as has cimetidine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…243 More recently it has been suggested that the production of nitric oxide by eosinophils may have a pathogenetic role. [261][262][263][264] Onset can be as early as the first day of life. 231,[245][246][247][248][249][250][251][252][253] It differs from the classic form (Ofuji's disease) by the severe pruritus, the absence of circinate and palmoplantar lesions, and the less frequent involvement of the face.…”
Section: Acne Fulminansmentioning
confidence: 99%
“…Several authors reported cases of this disease in immunocompromised or oncohaematological caucasian patients, either human immunodeficiency virus (HIV)‐positive or treated with immunosuppressory agents 2,3 . A childhood variant was also identified, characterized by the perinatal occurrence of lesions 4,5 . EPF has been rarely described in association with drug as carbamazepine 6 or allopurinol 7 …”
Section: Introductionmentioning
confidence: 99%